Deflation : Determinants, Risks, and Policy Options - Baig, Taimur (Occasional Papers; Occasional Paper, 2003)
Deflation can be costly and difficult to anticipate, and concerns of a generalized decline in prices in both industrial and emerging market economies have increased recently. This paper investigates the causes and consequences of deflation, the risk of deflation globally and in individual countries, and policy options. The authors discuss issues related to the measurement, determinants, and costs of deflation and examine previous episodes of deflation. They compute an index of deflation vulnerability, which they apply to the 35 largest industrial and emerging market economies. Finally, the paper offers several policy options for protecting against deflation and for coping with it should it strike.